Mesoporous TiO2 hierarchical structures: preparation and efficacy in solar cells. Issue 77 (20th October 2017) - Hwang, Dae-Kue; Kim, Jeong-Hwa; Kim, Kang-Pil; Sung, Shi-Joon
Abstract : We investigated an electrospray-based method to manufacture photoelectrodes for dye-sensitized solar cells (DSSCs). Abstract : We investigated an electrospray-based method to manufacture photoelectrodes for dye-sensitized solar cells (DSSCs). TiO2 doughnut-, spherical-, and disk-shaped particles with a large surface area, high crystallinity, uniform nanostructure, and good light scattering properties were fabricated via a simple electrospray method. The control of the morphology of the nanostructured particles prepared by electrospraying a dispersion of nanoparticles was investigated experimentally; the results are qualitatively explained on the basis of the available theory. The solvent in the droplet, droplet size, surface tension, process temperature, and process humidity are crucial to the morphology of the resulting particles. The effect of the particle morphology on the performance of DSSCs is demonstrated. Compared to the DSSCs with conventional photoelectrodes (with a power conversion efficiency of 8.4%), the DSSCs based on doughnut-, spherical-, and disk-shaped particle photoelectrodes yielded higher power conversion efficiencies of 8.8%, 9.3%, and 10.4%, respectively. The DSSC utilizing the disk-type photoelectrode showed the best performance under AM1.5 global illumination through a photo-mask at an illumination power of 100 mW cm −2 . This is because the generated TiO2 disks provide a large surface area and exhibit excellent light scattering capabilities, thus resulting in a low total internal resistance and long electron lifetime.